1991
DOI: 10.1038/sc.1991.91
|View full text |Cite
|
Sign up to set email alerts
|

Suicide following spinal cord injury

Abstract: SummaryA study of 9135 persons injured between 1973 and 1984 and treated at any of 13 model regional spinal cord injury (SCI) care systems was conducted. Follow-up ended December 31, 1985, by which time 50 persons had committed suicide (6'3% of deaths). Based on age-sex-race-specific rates for the general population, 10'2 suicides were expected to occur. Therefore, the standardized mortality ratio (SMR) for suicide was 4'9. The highestSMR occurred 1 to 5 years after injury. The SMR was also elevated for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 8 publications
4
61
0
3
Order By: Relevance
“…Some researchers have reported, perhaps counterintuitively, that people with high lesions have higher self-esteem and are more satisfied with their lives than people with incomplete or lower lesions [104][105][106] and that suicide rates among those with minimal impairments following SCI are nearly twice as high as among those with complete tetraplegia 107 (although the latter finding is not consistent across studies 108 ). While researchers have been at a loss to explain this paradox, it is possible that an inability to compete on an equal footing with able-bodied peers places particular distress upon those whose residual physical function suggests that this 'ought' to be attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported, perhaps counterintuitively, that people with high lesions have higher self-esteem and are more satisfied with their lives than people with incomplete or lower lesions [104][105][106] and that suicide rates among those with minimal impairments following SCI are nearly twice as high as among those with complete tetraplegia 107 (although the latter finding is not consistent across studies 108 ). While researchers have been at a loss to explain this paradox, it is possible that an inability to compete on an equal footing with able-bodied peers places particular distress upon those whose residual physical function suggests that this 'ought' to be attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Results showing individuals with tetraplegia to be at greater risk than those with paraplegia supported the ®ndings of several previous studies 9,10,12 whilst contradicting others. 4,11 Charlifue and Gerhart 12 have suggested that many of the risk factors for suicide such as alcohol and drug abuse, premorbid psychiatric illness, previous suicide attempts and family disintegration are not speci®c to SCI population, but pertain to general population as a whole. The increasing trend in rates of suicide in recent years has also been reported in other studies 13,14 and calls for better screening measures early after injury and during rehabilitation to identify individuals at increased risk, who require greater psychological support and more intensive follow up in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Well-being and adjustment were measured by self-report questionnaire, and included factors like adjustment, satisfaction with family relationships and social life, sexual activity, discrimination, depression, pain and feelings of dependency. Furthermore, suicide rates amongst persons with SCI may be four to ®ve times that of the age-sex-race-speci®c rates for the general population 2,3 and psychological factors are most likely related. 4 Research 5 has shown that mortality rates of SCI persons are signi®cantly higher for diseases like septicemia (82.2 times more likely), pneumonia (37.1 times) and pulmonary emboli (46.9 times more likely).…”
Section: Introductionmentioning
confidence: 99%